Transformasi Supervisi Pendidikan dalam Meningkatkan Mutu Sekolah: Integrasi Kepemimpinan, Profesionalisme Guru, dan Perspektif Global-Kontekstual: The Transformation of Educational Supervision in Enhancing School Quality: Integrating Leadership, Teacher Professionalism, and a Global-Contextual Perspective - Sudiansyah, Sudiansyah; Rostina, Rostina; Peterianus, Septian; Simin, Simin (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research examines the transformation of educational supervision in improving school quality through the integration of transformative leadership, teacher professionalism, and a global-contextual perspective. The background of the study is based on the paradigm shift in supervision from an administrative approach towards reflective and collaborative coaching. The purpose of this study is to explore the dynamics of implementing supervision that emphasizes coaching, professional dialogue, and the adoption of international practices within a local context. The research approach used is descriptive qualitative with data collection techniques through interviews, observation, and documentation studies, which are then validated through a member check and triangulation process. The results of the research indicate that school principals play a crucial role as collaborative leaders in shaping a participatory and reflective supervision ecosystem. Teachers experienced an increase in pedagogical and vocational capacity through PLC (Professional Learning Community) forums and practice-based coaching. Supervision is also beginning to be used as part of the internal quality assurance system. Structural obstacles such as time constraints and resistance are still encountered but can be overcome through innovative supervision strategies. In conclusion, an adaptive and contextual transformation of supervision is capable of driving continuous improvement in the quality of education.